ANALISIS RPP MATA PELAJARAN BAHASA JEPANG MAHASISWA PLP TAHUN 2019 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Dini Hanifah; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
ABSTRACT This qualitative descriptive research is purposed to describe two topics. The first one is the suitability Japanese subjects of the Lesson Plan used by teaching practice program in 2019 by Japanese Language Education Student with the standard of curriculum 2013. The second one is the suitability of the main activity in the Lesson Plan of Japanese subject with the basic competence of curriculum 2013. This research used documentation technique to collecting the data. Based on the formulation of the program, there are two findings of this research. The first finding shows that the Lesson Plan has 71, 5% of suitability with the curriculum 2013 which is still low.It happened because of the unsuitability in the aspect of time aloocation, basic competence, indicators of competence achievement, learning objectives, learning materials, and evaluation. The second finding display the unsuitability of the main activity with the basic competence of curriculum 2013. There are two factors that lead to this problem. The first factors is the absence ofscientific approach in the main activity. The second, the material that was delivered is not be found in the list of materials in curriculum 2013.Key Words: analysis, curriculum 2013, Japanese language, lesson plan